2012
DOI: 10.1124/mol.112.080317
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Low Open Probability of α7 Nicotinic Acetylcholine Receptors Can Be Overcome by Positive Allosteric Modulation and Serum Factors Leading to the Generation of Excitotoxic Currents at Physiological Temperatures

Abstract: ABSTRACT␣7 nicotinic acetylcholine receptors (nAChRs) have been a puzzle since their discovery in brain and non-neuronal tissues. Maximal transient probability of an ␣7 nAChR being open with rapid agonist applications is only 0.002. The concentration dependence of ␣7 responses measured from transfected cells and Xenopus laevis oocytes shows the same disparity in potency estimations for peak currents and net charge, despite being studied at 1000-fold different time scales. In both cases the EC 50 was approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 58 publications
(73 reference statements)
5
86
0
Order By: Relevance
“…Supporting this possibility of choline, PNU-120596 was recently reported to enhance the effects of subthreshold, physiologic concentrations of choline on native a7 nAChR in hypothalamic neurons . Although the enhancement seen using in vitro a7 nAChRs preparations is greatly decreased when experimental temperatures increase to near physiologic levels (Sitzia et al, 2011;Williams et al, 2012), apparently it is not completely eliminated given that PNU-120596 required enhanced endogenous a7 nicotinic activation to produce the antinociceptive effects in our tests. In addition, Williams et al, (2012) showed that, although the effects of PNU-120596 are strongly temperature dependent, physiologic factors, such as serum albumens, reverse this temperature dependency.…”
Section: Discussionmentioning
confidence: 97%
“…Supporting this possibility of choline, PNU-120596 was recently reported to enhance the effects of subthreshold, physiologic concentrations of choline on native a7 nAChR in hypothalamic neurons . Although the enhancement seen using in vitro a7 nAChRs preparations is greatly decreased when experimental temperatures increase to near physiologic levels (Sitzia et al, 2011;Williams et al, 2012), apparently it is not completely eliminated given that PNU-120596 required enhanced endogenous a7 nicotinic activation to produce the antinociceptive effects in our tests. In addition, Williams et al, (2012) showed that, although the effects of PNU-120596 are strongly temperature dependent, physiologic factors, such as serum albumens, reverse this temperature dependency.…”
Section: Discussionmentioning
confidence: 97%
“…The a7 receptors lack many of the specializations normally associated with ligand-gated ion channels that mediate fast synaptic transmission. Even under optimized conditions, a7 receptors have a probability of synchronized openings that is two orders of magnitude lower than that of the nAChRs at neuromuscular junctions or autonomic ganglia (Williams et al, 2012). They have five rather than two agonist binding sites, and although they desensitize rapidly at high levels of agonist occupancy, their desensitization is rapidly reversible and is not associated with the induction of a high-affinity nonconducting state.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated cytotoxic effects of PNU-120596 combined with choline on a7-expressing human embryonic kidney 293 (HEK 293) cells (Williams et al, 2012). This effect was blocked by the a7-selective competitive antagonist methyllycaconitine and was hypothesized to be due to ion channel-mediated calcium overload, similar to the NMDA receptor-mediated excitotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-attached Patch Clamp Electrophysiology-Cell-attached records were obtained from A7R3HC10 cells and HEK293 cells stably expressing human ␣7 and human RIC-3, as described previously (8). Cells were cultured in Dulbecco's modification of Eagle's medium (with 4.5 g/liter glucose, L-glutamine, and sodium pyruvate; Mediatech) supplemented with 10% heat-inactivated fetal bovine serum, 0.45 mg/ml geneticin-selective antibiotic (G418 sulfate; Gibco), and 0.015 mg/ml hygromycin B (Invitrogen), at 37°C with 5% CO 2 .…”
Section: -(4-(3-bromopropyl)phenyl)-3a459b-tetrahydro-3h-cyclopenmentioning
confidence: 99%
“…In contrast to synaptic-type nAChR, ␣7 receptors form as functional homopentameric receptors with five putative agonist-binding sites at the subunit interfaces (6). Activation of the ␣7 ion channel is most likely to occur with submaximal occupancy of the "orthosteric" agonist-binding sites (7), and even under optimal conditions, the channels activated by orthosteric agonists open with relatively low probability and for very brief periods of time compared with other nAChRs (8).…”
mentioning
confidence: 99%